Formamidinium Lead Iodide Perovskite Nanocrystal/Squaraine Dye Composite based Visibly Opaque and Near‐Infrared Transmitting Material. Issue 24 (27th October 2020) - Muthu, Chinnadurai; Pious, Johnpaul K.; Seethal, Parambatheri S.; Krishna, Nayana; Vijayakumar, Chakkooth
Abstract: Visibly opaque and near‐infrared transmitting (VONIRT) materials play a crucial role in forensic detection, security imaging, night‐vision photography, and biomedical applications. In this work, the development of such material using alpha‐formamidinium lead iodide based perovskite nanocrystals (PNCs) and squaraine (SQ) dyes is described. It is achieved by gradually increasing the size of PNCs followed by attaching them with a novel low‐bandgap SQ dye as capping ligand. The acid group present in the SQ dye efficiently interacts with the surface of the nanocrystals via non‐covalent interactions. Incorporation of SQ dyes onto PNCs yields composite films with uniform transmittance of below 2% in the visible region (380–740 nm) and above 60% in the NIR region, the prime requisites for VONIRT materials. Further, the addition of SQ dyes imparts better moisture stability and high film quality to the nanocrystals. Opaqueness in the visible region and excellent NIR transparency of the nanocomposite make them useful as a security material and for NIR photography application. Abstract : The development of visibly opaque and near‐infrared (NIR) transmitting material consisting of alpha‐formamidinium lead iodide based perovskite nanocrystals (PNCs) is described. It is achieved by gradually increasing the size of PNCs followed by attaching them with a novel low‐bandgap squaraine dye as capping ligand. The suitability of this material for security and NIR photography applications is demonstrated.